Isolated high altitude psychosis, delirium at high altitude, and high altitude cerebral edema: are these diagnoses valid? - Hüfner, Katharina; Falla, Marika; Brugger, Hermann; Gatterer, Hannes; Strapazzon, Giacomo; Tomazin, Iztok; Zafren, Ken; Sperner-Unterweger, Barbara; Fusar-Poli, Paolo (Frontiers in Psychiatry, 2023)
Psychosis is a psychopathological syndrome that can be triggered or caused by exposure to high altitude (HA). Psychosis can occur alone as isolated HA psychosis or can be associated with other mental and often also somatic symptoms as a feature of delirium. Psychosis can also occur as a symptom of high altitude cerebral edema (HACE), a life threatening condition. It is unclear how psychotic symptoms at HA should be classified into existing diagnostic categories of the most widely used classification systems of mental disorders, including the Diagnostic and Statistical Manual of Mental Disorders (DSM-V) and the International Statistical Classification of Diseases and Related Health Problems (ICD-11). We provide a diagnostic framework for classifying symptoms using the existing diagnostic categories: psychotic condition due to a general medical condition, brief psychotic disorder, delirium, and HACE. We also discuss the potential classification of isolated HA psychosis into those categories. A valid and reproducible classification of symptoms is essential for communication among professionals, ensuring that patients receive optimal treatment, planning further trips to HA for individuals who have experienced psychosis at HA, and advancing research in the field.